RESTRICTION WOULD STRENGTHEN THE PROFESSION. - Hope, J. William (The Accounting Review, 1945)
Abstract According to the author accounting profession would be strengthened and the public interest would be better served, if all persons who present themselves as practitioners of public accountancy would be required by law, first to demonstrate their professional abilities and then to act in accordance with recognized standards of practice. Accountancy is not an exact science. There are no set rules or formulae, which can be used as a guide by the untrained. It follows, then, that the public accepts the practitioner pf public accountancy in good faith as one properly qualified to render a specialized service, important to the welfare of business and, consequently to the general public. The present generation should accept this, even though it means that they will encounter the many difficulties concomitant with such a drastic change as the regulation of practice through restrictive legislation. They should work and strive with all the ability they possess and the strength of character, which has been built into their profession to bequeath to the certified public accountants of the future the gracious heritage of a unified profession.